Productive performance and nutritional value of seven clover genotypes in three altitudinal floors of the northern highlands of Peru - Vallejos Fernández, Luis Asunción (2021)
The aim of this study was to evaluate the productive performance and nutritional value of seven clover genotypes at three altitude levels (PA I: 2300-2800 m above sea level, PA II: 2801-3300 and PA III: 3301-3800) of the northern highlands of Peru during a year. Four genotypes of white clover (Trifolium repens) and three genotypes of red clover (Trifolium pratense) were installed in each altitudinal floor (PA). The germination power, weight and purity of the seeds were evaluated to ensure the viability of the number of seeds sown. The yield (kg DM ha-1 year-1), growth rate (kg DM ha-1 day-1), plant height (cm) and nutritional value for each genotype were determined. The highest yields and the best growth rates (p<0.01) in the three PAs corresponded to the three varieties of Trifolium pratense (Tuscan, Americano and Relish). PA I (p<0.01) obtained the highest dry matter production (12 340.6 kg DM ha-1 year-1), followed by PA II (7808.4 kg DM ha-1 year-1) and PA III (3923.4 kg DM ha-1 year-1), showing the same trend for the growth rate (p<0.01). Crude protein levels ranged from 19.75 to 23.77% (p=0.009). The results indicate that all genotypes of Trifolium pratense and Trifolium repens should be considered as a good alternative to associate with pastures in the highlands of northern Peru.